2013
DOI: 10.1128/aem.02404-13
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Genetic Diversity of Arcobacter butzleri in an Artisanal Dairy Plant in Italy

Abstract: bThe present study aimed to investigate the presence, distribution, and persistence of Arcobacter spp. in an artisanal dairy plant and to test the isolates to determine their different genotypes in the processing plant and in foods. Samples were collected in an artisanal cheese factory on four occasions between October and December 2012. Food samples (raw milk, ricotta cheese, mozzarella cheese, and conditioning liquid), water samples, and environmental samples were analyzed by the culture method; isolates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 24 publications
5
45
1
Order By: Relevance
“…This study showed the occurrence of A. butzleri in the surfaces of the investigated dairy plant, in agreement with previous reports (10)(11)(12) in which A. butzleri was isolated from surfaces in contact with food and from surfaces not in contact with food both in artisanal and in industrial dairy plants; the plant surfaces were more frequently contaminated than food samples (33.3% versus 21%).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This study showed the occurrence of A. butzleri in the surfaces of the investigated dairy plant, in agreement with previous reports (10)(11)(12) in which A. butzleri was isolated from surfaces in contact with food and from surfaces not in contact with food both in artisanal and in industrial dairy plants; the plant surfaces were more frequently contaminated than food samples (33.3% versus 21%).…”
Section: Discussionsupporting
confidence: 80%
“…Although the present study did not investigate the primary source of dairy plant contamination, postprocess contamination was identified as the most probable source of ricotta cheese contamination, in agreement with a previous study (10). In fact, the survival of A. butzleri during the cheese manufacturing process can be excluded given the thermal treatment applied to produce ricotta cheese (heating at 80 to 82掳C of a 1,500-liter vat of whey) and the thermal resistance of A. butzleri (33) that was reported to have a decimal reduction time at 55掳C between 0.4 and 1.1 min and a Z value between 7.4 and 8.1掳C, in the stationary and exponential phases, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations